2015
DOI: 10.1021/acs.jpcc.5b01402
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Adsorption on Copper Surfaces as the First Step during the Deposition of Copper: A Density Functional Study with van der Waals Correction

Abstract: Copper dimethylamino-2-propoxide [Cu(dmap) 2 ] is used as a precursor for low-temperature atomic layer deposition (ALD) of copper thin films. Chemisorption of the precursor is the necessary first step of ALD, but it is not known in this case whether there is selectivity for adsorption sites, defects, or islands on the substrate. Therefore, we study the adsorption of the Cu(dmap) 2 molecule on the different sites on flat and rough Cu surfaces using PBE, PBE-D3, optB88-vdW, and vdW-DF2 methods. We found the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 58 publications
4
39
0
Order By: Relevance
“…41 We found that pure PBE predicts that physisorbed and chemisorbed structures exist on the flat Cu (111) surface depending on the adsorption sites. We also found from the Bader charge analysis that the 13 and decomposition (B1 and B2) are in Figure 3.…”
Section: Adsorption and Decomposition Of Cu(dmap) 2 On Cu(111) Surfacementioning
confidence: 84%
See 3 more Smart Citations
“…41 We found that pure PBE predicts that physisorbed and chemisorbed structures exist on the flat Cu (111) surface depending on the adsorption sites. We also found from the Bader charge analysis that the 13 and decomposition (B1 and B2) are in Figure 3.…”
Section: Adsorption and Decomposition Of Cu(dmap) 2 On Cu(111) Surfacementioning
confidence: 84%
“…This involves the loosing of Cu -N coordination and the formation of metallic bonds from adsorbate Cu to surface Cu as described in detail in Ref 41 . Figure 2 shows that the transformation needs a small activation energy of 0.17 eV, which can be overcome at a typical ALD temperature, e.g.…”
Section: Adsorption and Decomposition Of Cu(dmap) 2 On Cu(111) Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the adsorption energies and geometries depend on the roughness of the surface and on the method to treat the van der Waals interaction in DFT. 20 Strong distortion of the molecule and cleavage of Cu− −N bonds is predicted in the chemisorbed structures, which allows these parts of the ligand to lift off the surface and avoid Cu− −C bonding, but also become reactive towards the co-reagent. The molecule gains linear O− −Cu− −O bonding and this is where charge redistribution with the surface mainly occurs.…”
Section: Redox Adsorption Of Metal Precursormentioning
confidence: 99%